Sustainability assessment of residential buildings : methodology SBTool Portugal - Mateus, Ricardo (2008)
The purpose of a sustainability assessment is to gather and report information for during different phases of construction, design and use of a building. The sustainability scores or profiles based on indicators result from a process in which the ant phenomena are identified, analyzed and valued. Following a life-cycle-analysis or analysis of chosen indicators, a building can be assessed, rated and certified. The benefits of rating tools are that various kinds of sustainability and performance issues n be included in the assessment criteria and their use is in common user-friendly, to the extent that self-evaluation tools are available in the Internet paper aims to present a novel approach to develop building sustainability Assessment and rating and contributes to the evolution of generic methodology and international understanding by introducing an approach to take the different dimension of sustainability into account. The scope of the methodology that is going to be presented (SBToolPT) is to assess the sustainability of existing, new and renovated buildings in the urban areas and especially in the Portuguese context. This new methodology is intended to foster the awareness of the Portuguese construction market stakeholders and to allow adequate policy implementation on sustainable construction.